Implementation of the Problem-Based Learning (PBL) Model to Improve Conceptual Understanding and Student Activeness in Grade X - Rohim Rohim; Aniza Haridha Zain; Chairatul Umamah; Ifa Tachwifa; Agustina Widiastutie (Lombok Institute, 2025)
This study aimed to improve students' conceptual understanding and learning activeness in Biology in a Grade X class at SMAN 3 Pamekasan by implementing the Problem-Based Learning (PBL) model on the topic of environmental change. Classroom action research was employed to examine improvements in conceptual understanding and students' active participation during instruction. Data were collected through observation and written tests administered within the PBL implementation. Essay test scores and observation sheets were presented in tables and graphs to facilitate analysis. In Cycle I, the mean score for students' conceptual understanding reached 86.33 and increased in Cycle II to 92.39, indicating a high level of mastery. Meanwhile, student activeness in Cycle I was 64% (categorized as